Konstruksi dan Validasi Model Desain Pembelajaran Berbasis Masalah untuk Mengembangkan Kreativitas Siswa - Ika Kartikasari; M. Rusdi; Rayandra Asyhar (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
The aims of this research are to construct and validate an instructional design model that incorporates the theory and practice of Problem-Based Learning (PBL) approach and provides a framework for the internal validation of instructional design model using expert and practitioners review procedures. The research consisted of three phases. In phase one, the theoretical foundations of Problem-Based Learning (PBL) approach and instructional design were examined to guide the development of such model. In phase two, the model components were determined and an initial model was constructed. In phase three, the model was reviewed and validated by expert and practitioners in the field of instructional design through a three-round Delphi study. The result was a revised and validated Problem-Based Instructional Design Model to develop students’ creativity and provide the process of the internal validation of instructional design model.